2022
DOI: 10.1021/acs.iecr.2c01885
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Fabrication of an MXene-ZrP@PDA Heterojunction for Enhanced Corrosion/Wear Resistance of Waterborne Epoxy Coatings

Abstract: Two-dimensional (2D) materials have a wide range of applications in the field of corrosion protection and wear resistance. The use of MXene (Ti 3 C 2 T x ) in epoxy coatings is limited due to its natural restacking tendency. Herein, MXene-ZrP@ PDA was obtained through the polydopamine (PDA) functionalization of a heterojunction composed of MXene and exfoliated αzirconium phosphate (α-ZrP). MXene-ZrP@PDA (MZP) was incorporated into a waterborne epoxy (WEP) coating to prepare an MZP/WEP composite coating. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Meanwhile, the P−O stretching vibration peak and the characteristic peak of the benzene ring were observed at 1049 and 1470 cm −1 , respectively. 39,40 The above results indicated that BTA-P 4444 -Lig was successfully loaded into the f-MXene.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…Meanwhile, the P−O stretching vibration peak and the characteristic peak of the benzene ring were observed at 1049 and 1470 cm −1 , respectively. 39,40 The above results indicated that BTA-P 4444 -Lig was successfully loaded into the f-MXene.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…In Fig. 4B, compared with previously reported disordered functionalized MXene/EP composite coatings, [9][10][11][12][13][15][16][17][18]21 the OMC coating has the highest SZ value because of its more effectivity and efficiency. This is not only due to the low porosity of the coating matrix, but also due to the optimized "maze effect" of MXene nanosheets by ordered arrangement.…”
Section: Electrochemical Behaviours Of Coatingsmentioning
confidence: 65%
“…Covalent bonding and electrostatic adsorption were also combined to enhance the barrier and anticorrosion performance of MXene/EP coatings such as zirconium phosphate (α-ZrP) @MXene hybrids via polydopamine (PDA) functionalization. 21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…140 We prepared polydopamine (PDA) modified MXene-ZrP composites using a one-pot method and applied the MXene-ZrP@PDA (MZP) heterojunction to enhance the corrosion and wear resistance of waterborne epoxy coatings. 141 The corrosion test results indicated that the corrosion rate of the MZP/WEP composite coating was reduced by an order of magnitude compared with the blank WEP coating. The two-dimensional nanosheet materials can extend the diffusion path of the corrosion media.…”
Section: Reviewmentioning
confidence: 98%